The intimacy of consciousness exploration and transpersonal psychotherapy : coming home - Jahrsetz, Ingo B.; Hess, Regina U. (Cambridge Scholars Publishing, 2017)
This volume brings together a group of transpersonal psychotherapists and spiritual teachers to tell of their own very personal and intimate explorations of consciousness. What has the experience of ""coming home"" meant to them? Has it meant connecting with God, the Divine Feminine, the Cosmos, the Sacred? Has it meant arriving at home in themselves, in their very center, in their essence? Where is home? Is it inside, is it outside, or is it both? All world cultures have stories about this particular place. In addition to describing their own unique quests, the contributors also share how radi.